TREATMENT AND PREVENTION OF OSTEOCHONDROSIS OF THE NECK. - Turgunov Zokirjon Alimjonovich; Khodjaeva Naimakhon Umirzakovna; Izzatullaeva Dilfuza Nematovna (Western European Studies, 2024)
Osteochondrosis of the cervical spine is a degenerative condition impacting the intervertebral discs and surrounding structures. It presents with symptoms like neck pain, restricted movement, and neurological deficits due to nerve compression. This article reviews current treatments and prevention strategies, supported by recent literature. Effective management includes conservative approaches, exercise, physiotherapy, and, in advanced cases, surgical intervention. Preventative measures focus on lifestyle adjustments, ergonomic practices, and strengthening exercises.
Keywords: Cervical osteochondrosis; neck pain; degenerative disc disease